A CBR approach based on ontology to supplier selection - BEKKAOUI, Mokhtaria; KARRAY, Mohamed Hedi; MELIANI, Sidi Mohammed (University of Eloued جامعة الوادي, 2022)
Most previous research categorizes supply chain management (SCM) into the following three major parts: purchasing, manufacturing, and distribution. In the purchasing process, supplier selection represents a crucial step for enhancing firms’ competitiveness.An increasing number of researches have been devoted to the development of different methodologies to cope with this problem.The majority of research explores the difference in the set of criteria for supplier selection. They used famous methods for selection such as AHP (Analytic Hierarchy Process); ANP (Analytic Network Process); DEA (Data Envelopment Analysis);TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). Thus, this paper presents a CBR (Case Based Reasoning) approach in the context of supplier selection decision making.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Supplier selection · Ontology · Experience Feedback (EF) · CBR